Working with farmers for agricultural innovation and climate adaptation - Vermeulen, Sonja J.; Wynter, A (2014)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), in common with other CGIAR research programs, understands that farmers are at the centre of agricultural innovation and adaptation. This publication describes some of the many ways in which CCAFS works with farmers and farmers’ organizations to solve problems generated by climate change. Recognizing the importance of participatory knowledge systems involving farmers, scientists, and other stakeholders in responding effectively to climate change, this document seeks to provide an overview of the many ways CCAFS collaborations with farming communities work in practice – and how this can serve as a springboard for more effective dialogue and planning, leading ultimately to better outcomes for farming in a climate-constrained world.